Alauda arvensis subsp. hainana Hartert ... - LeCROY, M. A. R. Y. (Zenodo, 2003)
Alauda arvensis hainana Hartert Alauda arvensis hainana Hartert, 1922a: 21 (KiungChau, Hainan). Now Alauda gulgula sala Swinhoe, 1870. See Peters, 1960a: 70, Cheng, 1987: 427, and Dickinson et al., 2001a: 93. LECTOTYPE: AMNH 555556, adult male, collected at Ch’iungchou, 19°56′N, 110°30′E (Times Atlas), Hainan Island, China, on 24 February 1902, by Zensaku Katsumata. From the Rothschild Collection. COMMENTS: Hartert (1922a: 21) noted that he had 12 specimens of this form and that the type was a male collected at KiungChau, Hainan, on 24 XI [sic] 1902 by Katsumata. There are 12 specimens collected by Katsumata on Hainan in February and March 1902 now in AMNH, although three of them are from Haihow, not Ch’iungChau. Hartert (1928: 201) designated as lectotype a male from ‘‘Kiangchau’’ collected on 24 February 1902, correctly citing the collecting date. There are three males collected on this date, but AMNH 555556 is the specimen bearing the Rothschild type label. The Rothschild Collection label is also ... : Published as part of LeCROY, M. A. R. Y., 2003, TYPE SPECIMENS OF BIRDS IN THE AMERICAN MUSEUM OF NATURAL HISTORY. PART 5. PASSERIFORMES: ALAUDIDAE, HIRUNDINIDAE, MOTACILLIDAE, CAMPEPHAGIDAE, PYCNONOTIDAE, IRENIDAE, LANIIDAE, VANGIDAE, BOMBYCILLIDAE, DULIDAE, CINCLIDAE, TROGLODYTIDAE, AND MIMIDAE, pp. 1-156 in Bulletin of the American Museum of Natural History 278 (278) on pages 27-28, DOI: 10.1206/0003-0090(2003)278<0001:tsobit>2.0.co;2, http://zenodo.org/record/13256611 ...